Code Switching in BIPA Classes: Teachers' and Students’ Attitudes - Hanna Suteja; Christina Purwanti (Polyglot, 2017)
The controversy of using L1 or L2 only in second language classes has been widely discussed in many studies. Some teachers, however, opt for the middle ground by employing the bilingual approach; they practice code switching to some extent to facilitate teaching learning process.  In the context of BIPA teaching and learning this issue has not been sufficiently addressed. Therefore, this study seeks to explore the teachers as well as the students’ attitude towards the practice of code-switching in BIPA classes, specifically in the basic level classes. The factors behind its practice will also be discussed in the light of its benefit and hindrance for teaching learning process. This study employed a quantitative research design by conducting a survey and a qualitative research design by interpreting the result of the interview with the teachers and students. In general the study indicates the need of code-switching to support teaching and learning process, especially for the beginner level classes.BAHASA INDONESIA ABSTRAK: Kontroversi penggunaan hanya bahasa pertama atau bahasa kedua dalam kelas bahasa kedua telah banyak dibahas dalam banyak penelitian. Meskipun demikian, sebagian pengajar memilih jalan tengah dengan menggunakan pendekatan dwi-bahasa; mereka menggunakan alih kode sampai kadar tertentu untuk memudahkan proses belajar mengajar. Dalam konteks belajar mengajar BIPA isu ini kurang banyak dibahas. Karena itu, studi ini ingin mengkaji sikap para pengajar maupun pelajar terhadap praktek alih kode di kelas BIPA, khususnya di kelas tingkat  dasar. Faktor-faktor di balik praktek tsb juga akan dibahas dalam perspektif kelebihan dan kekurangannya untuk proses belajar mengajar. Penelitian ini bersifat kuantitatif dengan mengadakan survei dan juga kualitatif dengan melakukan intepretasi terhadap hasil wawancara dengan pengajar dan pelajarnya. Secara umum, studi ini mengindikasikan perlunya alih kode untuk mendukung proses belajar mengajar, khusunya untuk kelas tingkat dasar.